Podoplanin is expressed at the invasive front of esophageal squamous cell carcinomas and is involved in collective cell invasion. Issue 12 (22nd October 2013) - Nakashima, Yuichiro; Yoshinaga, Keiji; Kitao, Hiroyuki; Ando, Koji; Kimura, Yasue; Saeki, Hiroshi; Oki, Eiji; Morita, Masaru; Kakeji, Yoshihiro; Hirahashi, Minako; Oda, Yoshinao; Maehara, Yoshihiko
<x xml:space="preserve">Abstract</x> The expression of podoplanin is reportedly involved in collective cell invasion, which is independent from the epithelial–mesenchymal transition (EMT). We focused on the expression of podoplanin in esophageal squamous cell carcinomas (ESCC) and investigated the correlation of podoplanin and EMT‐related markers, and evaluated its prognostic significance. Five ESCC cell lines were subjected to western blot analysis for podoplanin and EMT markers. The effects of podoplanin on EMT and carcinoma invasion were evaluated with wound healing assays, invasion assays and 3‐D culture. Transfection of ectopic podoplanin into a podoplanin‐negative ESCC cell line (TE‐15) induced cell migration and invasive activity (P < 0.001 and P < 0.05, respectively) without downregulation of E‐cadherin. In contrast, transfection of si‐podoplanin RNA into a podoplanin‐positive ESCC cell line (TE‐13) reduced cell migration and invasive activity (P < 0.05). We reviewed 101 patients who had undergone esophagectomy for ESCC. Podoplanin expression was observed in 58 patients (57.4%), and positive expression was positively correlated with expression of E‐cadherin (P < 0.01), deeper wall invasion (P < 0.01), venous invasion (P < 0.05) and poorer prognosis (P < 0.01). Multivariate Cox analysis revealed that expression of podoplanin was a significant and independent unfavorable predictor of survival (P < 0.05). These data suggest that podoplanin is significantly associated with and likely contributes to ESCC invasion in the absence of EMT.